Jobs and competitiveness in a polarised Europe - Valeria Cirillo; Dario Guarascio (Intereconomics, 2015)
In the aftermath of the crisis, Europe is becoming more polarised in terms of employment, competitiveness and industrial specialisation. A 'German-centred core' which maintained employment and production - has emerged, contrasted by a 'Southern periphery', where major economic losses have occurred. Such geographical divergence is associated with a further polarisation in terms of skills. A new European industrial policy is needed to reverse this polarisation process and its dangerous implications for trade balances and cohesion.
Keywords: 330; Arbeitskräfte; Internationaler Wettbewerb; Industriepolitik; Europa